The Art of Being Free : Taking Liberties with Tocquevile, Marx, and Arendt - Reinhardt, Mark (Contestations, 2019)
The "art of being free" is an essential part of democracy. It involves, Mark Reinhardt believes, bringing into being the multiple spaces in and practices through which individuals and groups help to constitute their lives, their selves, their worlds. Americans are presently witnessing a contraction of officially sanctioned spaces for citizen action. It is now crucial, Reinhardt argues, to identify ways of opening new spaces for the direct practice of democratic politics.Reinhardt treats the writings of Alexis de Tocqueville, Karl Marx, and Hannah Arendt as exemplary sources for an expansion of political possibility. These writers indicate where and how the new spaces can be brought into being, and they reveal acts of making space as some of the prime moments of politics. Reinhardt's extended readings of these writers, never previously treated together, are quite unlike the familiar understandings of their thought. "Taking liberties," he brings the literary and political sensibility usually associated with postmodernism to a sympathetic if critical encounter with eminently modern thinkers. The result is a strong and idiosyncratic book, accessible and stylish, that mixes acute readings of canonical thinkers with more practical applications and illustrations. Reinhardt combines attention to textual detail and nuance with concern for contemporary politics, discussing as an unusually inventive example the AIDS activist group ACT UP.